Non-healing arm wound with a discharging sinus in an elderly patient with diabetes - Bansal, Shaifali (BMJ Publishing Group, 2010)
A 48-year-old Filipino female presented with unilateral acute onset painful red eye, blurred vision and yellow discharge. On examination she had a corrected visual acuity of 6/5 in the right eye and 6/18 in the left eye. There was a left-sided periorbital swelling, with chemosis involving the bulbar conjunctiva on the temporal aspect. Ocular motility showed limitation of left-sided abduction with mild limitation of laevoelevation and laevodepression. She was afebrile and systemic examination was unremarkable. Medical history included diagnosis of Crohn's disease since the age of 20. She was on oral mesalamine 1 g for mildly active colitis. Full blood count was normal but erythrocyte sedimentation rate and C reactive protein were raised. Blood culture and conjunctival swab were negative. Contrast-enhanced CT scan demonstrated enlargement of the lacrimal gland. She was managed conservatively with acetaminophen and codeine for pain and swelling. She recovered completely in 2 weeks with no sequelae.